The Effect of Goal orientation and Motivation of Female Footballers in Sports on Resilience Power - Yeşim Bayrakdaroğlu; Ahmet Yilmaz Albayrak; Ali Tekin; Efecan Tezcan (Türk Spor ve Egzersiz Dergisi)
The aim of this study is to investigate the effect of goal orientation and motivation of female footballers in sports on resilience power. In the study, there 183 female footballers based upon the leagues Süper Lig (Super League), PTT 1st League, 3rd League and Amateur League. As data collection tools, Resilience Scale, Task and Ego Orientation in Sport Questionnaire and Sport Motivation Scale were used. The results were obtained through One-way ANOVA and Regression analyses. As a result of the analyses, the female footballers have significant, positive and low level correlation between goal orientation and resilience; on the other hand, there is a significant, positive and very low level correlation between goal orientation and sport motivation (p lt;0,05). A significant, positive and low level correlation among the mean scores of resilience, goal orientation and sport motivation (p lt;0,05). There is a significant, positive and low level correlation between sport motivation and goal orientation (p lt;0,05). As a consequence of the results obtained, various suggestions are made in order to shed a light on the possible future studies.